2009
DOI: 10.1007/s11926-009-0041-1
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory milieu in idiopathic inflammatory myositis

Abstract: The idiopathic inflammatory myopathies (IIM) are systemic autoimmune diseases that have predominant mononuclear inflammatory cell infiltrates in the skeletal muscle. The cells that are typically involved in the pathogenesis of disease are B-lymphocytes, T-lymphocytes, macrophages, dendritic cells, and natural killer cells. However, in addition to these immune cells, cells of nonimmunologic origin, such as myocytes, may be directly involved in the immune response. The local milieu also consists of distinct cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…This trans-presentation is anticipated to be relevant for T cells as they express IL-2Rβ and γc subunits on their cell membrane 17 32. T cell infiltration in skeletal muscle is a characteristic histopathological feature of PM/DM 33. T cells usually maintain a state of homeostasis even after IS treatment, as shown by our data in this study and in a previous report 34.…”
Section: Discussionsupporting
confidence: 75%
“…This trans-presentation is anticipated to be relevant for T cells as they express IL-2Rβ and γc subunits on their cell membrane 17 32. T cell infiltration in skeletal muscle is a characteristic histopathological feature of PM/DM 33. T cells usually maintain a state of homeostasis even after IS treatment, as shown by our data in this study and in a previous report 34.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast to DM, CD4 þ T cells and B cells are known to predominate in the perivascular areas of the muscle tissue. 36 Nevertheless, there remains much about pathogenesis to be learned in ILD in PM/DM, which might differ from mechanisms in the lung. A recent study showed low counts of peripheral T cells and a low percentage of CD4 þ T cells were associated with the presence of ILD in PM/DM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, endomysial infiltratesfound predominantly in polymyositis and sIBM-are mainly composed of CD8 + T cells, CD4 + T cells, dendritic cells (DCs) and macrophages, whereas the peri vascular infiltrates that predominate in dermatomyositis are mainly composed of CD4 + T cells, DCs, and macro phages, with occasional B cells ( Figure 1). [10][11][12] …”
Section: Immune Mechanismsmentioning
confidence: 99%